Knowledge about the Bible and Skills for Biblical Interpretation Imparted by Norwegian RE Textbooks for Upper Secondary Education - Hartvigsen, Kirsten Marie (Religious education, 2020)
This qualitative study investigates the knowledge about the Bible and the skills required for biblical interpretation as imparted by three textbooks for Norwegian upper secondary religious education (RE). The multidimensional theoretical framework combines models from biblical hermeneutics and RE. One model distinguishes between the worlds behind, in, and in front of the biblical text. Another distinguishes between the universal, common religious, and religion-specific dimensions of religious narratives. While the body texts alternate between the worlds behind, in, and in front of the text, the assignments focus on the worlds in and in front of the text and the religion-specific dimension.